2000
DOI: 10.1002/1521-3765(20001002)6:19<3558::aid-chem3558>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A molecular-level abacus-like system driven by light inputs has been designed in the form of a [2]rotaxane, comprising the pi-electron-donating macrocyclic polyether bis-p-phenylene-34-crown-10 (BPP34C10) and a dumbbell-shaped component that contains 1) a Ru(II) polypyridine complex as one of its stoppers in the form of a photoactive unit, 2) a p-terphenyl-type ring system as a rigid spacer, 3) a 4,4'-bipyridinium unit and a 3,3'-dimethyl-4,4'-bipyridinium unit as pi-electron-accepting stations, and 4) a tetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
203
1
2

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 326 publications
(219 citation statements)
references
References 17 publications
13
203
1
2
Order By: Relevance
“…Electrochemical and NMR spectroscopic data showed (29) that the stable conformation of 1 6ϩ is by far the one in which the R component is located around the better electron acceptor station, A 1…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrochemical and NMR spectroscopic data showed (29) that the stable conformation of 1 6ϩ is by far the one in which the R component is located around the better electron acceptor station, A 1…”
Section: Resultsmentioning
confidence: 99%
“…In a previous work (29), we reported on the rotaxane 1 6ϩ (Scheme 1) that was carefully designed and synthesized to perform as a linear molecular motor powered exclusively by visible light, with autonomous operation relying on intramolecular processes. In such a work, however, we only succeeded in demonstrating the operation of the rotaxane as a light-driven mechanical switch that needed alternate addition of two ''fuels,'' namely triethanolamine and oxygen, with concomitant generation of waste products.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10] In parallel, several groups have shown that it is possible realize complex combinational logic circuits at the molecular scale, up to half and full addition or subtraction using various external perturbations, i.e., chemical, biochemical, photochemical, optical, electrochemical, electrical, to address the system, encode the inputs and perform the logic operations. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] We propose here another approach for implementing molecular logic gates.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the experience gained with pseudorotaxane model systems [62], the rotaxane 19 6þ (Figure 1.17) was specifically designed [63] to achieve photoinduced ring shuttling in solution. This compound has a modular structure; its ring component R is a p-electron-donating bis-p-phenylene [34]crown-10, whereas its dumbbell component is made of several covalently linked units.…”
Section: 85mentioning
confidence: 99%
“…The molecular shuttle 19 6þ can also be operated, with a higher quantum yield, by a sacrificial mechanism [63] based on the participation of external reducing (triethanolamine) and oxidizing (dioxygen) species and by an intermolecular mechanism [64] involving the kinetic assistance of an external electron relay (phenothiazine), which is not consumed. However, operation by the sacrificial mechanism does not afford an autonomous behavior and leads to consumption of chemical fuels and formation of waste products.…”
Section: 85mentioning
confidence: 99%